Altered maturation and activation state of circulating monocytes is associated with their enhanced recruitment in pulmonary arterial hypertension - Harper, Rebecca L.; Zhou, Xin; Marciano, David P.; Cao, Aiqin; Wang, Lingli; Chen, Guibin; Adil, Mir S.; Zhou, Wenyu; Maguire, Peter; Deivanayagam, Shanthi; Yu, Quan; Viswanathan, Vignesh; et al. (Respiratory research, 2025)
It is well-established that patients with pulmonary arterial hypertension (PAH) exhibit increased recruitment of circulating monocytes to their pulmonary arteries. However, it remains unclear whether these monocytes have intrinsic abnormalities that contribute to their recruitment and to PAH pathogenesis. This study aimed to characterize the gene expression profiles of circulating classical, intermediate, and non-classical monocytes and assess their maturation trajectory in patients with idiopathic (I) PAH compared to control subjects. Additionally, it sought to explore the relationship between the observed IPAH abnormalities and deficiencies in bone morphogenetic receptor 2 (BMPR2), the most frequently mutated gene in PAH, and to assess adhesion and transendothelial migration, key processes in monocyte infiltration of pulmonary arteries. Differentially expressed genes and maturation trajectories of circulating monocytes from patients with IPAH vs. control subjects were compared using single cell RNA sequencing (scRNAseq), followed by FACS analysis. Observations from IPAH and control cells were related to reduced BMPR2 using a THP1 monocyte cell line with BMPR2 reduced by siRNA as well as induced pluripotent stem cell (iPSC) derived monocytes (iMono) from hereditary (H) PAH patients with a BMPR2 mutation and monocytes from mice with Bmpr2 deleted (MON-Bmpr2 ). Classical IPAH monocytes have decreased CD14 mRNA leading to a deviation in their maturation trajectory and early terminal fate, which is not rescued by cytokine treatment. Monocytes that evade early cell death show elevated STAT1, PPDPF and HLA-B, and an interferon (IFN) signature indicative of an altered activation state. A strong link between decreased BMPR2 and CD14 was observed in THP1 cells and in HPAH iMono with a BMPR2 mutation associated with STAT1 and IFN related genes, and in monocytes from MON-Bmpr2 mice. Increased adhesion to iPSC-derived endothelial cells (iECs) in HPAH-BMPR2 mutant iMono was associated with elevated ICAM1 expression. Enhanced transendothelial migration of these cells was associated with the reduction in endothelial VE-cadherin (CDH5). IPAH monocytes exhibit an altered activation state associated with reduced BMPR2 and CD14, along with elevated STAT1-IFN expression. These changes are linked to intrinsic functional abnormalities that contribute to the monocytes' increased propensity to invade the pulmonary circulation.